Hathor's alchemy : the ancient Egyptian roots of the hermetic art - Roberts, Alison (NorthGate Publishers, 2019)
Ever since alchemy first emerged in Graeco-Roman Egypt, alchemists have said their wisdom came from the pharaonic temples. Yet though the West has had unprecedented access to this hidden knowledge since the decipherment of hieroglyphs, ancient Egypt's connection with alchemy still remains obscure, doubted even by many. Focussing on the beautiful temples at Abu Simbel and Dendara, dedicated to the fiery serpent-eye goddess Hathor, this groundbreaking book explores for the first time the legacy left to alchemists by the pharaohs. It also goes deep into Ramesses VI's extraordinary tomb at Thebes to discover the secrets of growth and renewal guarded by Osiris and vivified by Hathor's copper love. Both metallurgical and mystical, these sacred secrets laid the foundations for the Hermetic art. The transmission initially came through Graeco-Egyptian and Jewish alchemists, then Islamic adepts, many of whom were Sufis belonging to an Akhmim alchemical lineage, until eventually Hathor's alchemy reached medieval Europe to inspire the 'rising dawn' tradition. And with a spiritual vision grounded in nature, it still has vital relevance for our world today.